1991
DOI: 10.1002/gcc.2870030304
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of 434 consecutively ascertained specimens of non‐Hodgkin's lymphoma: Correlations between recurrent aberrations, histology, and exposure to cytotoxic treatment

Abstract: Cytogenetic abnormalities in non-Hodgkin's Lymphoma (NHL) provide a model system for the analysis of the role of multiple genomic aberrations in human malignancy. In order to define correlations with histology, tumor evolution, and the effects of genotoxic exposure, cytogenetic analysis was performed on 434 specimens of NHL derived from 423 patients consecutively ascertained over a 5-year period (1984-1989). Six recurring translocations (RT) were observed: t(14;18)(q32;q21), t(8;14)(q24;q32), t(11;14)(q13;q32)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
119
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(133 citation statements)
references
References 30 publications
13
119
0
1
Order By: Relevance
“…This chromosomal aberration is a common change in retinoblastoma, but rarely occurs in acute lymphoblastic leukaemia and lymphoma (Heim & Mitelman, 1995;Fifth International Workshop on Chromosomes in LeukemiaLymphoma, 1987;Offit et al, 1991). In a previous report (Tien et al, 1993), one of four patients with EBV-associated T-cell malignancies (nasal lymphoma was not included in that study) showed isodicentric chromosome 6, idic(6)(pter !…”
Section: Discussionmentioning
confidence: 97%
“…This chromosomal aberration is a common change in retinoblastoma, but rarely occurs in acute lymphoblastic leukaemia and lymphoma (Heim & Mitelman, 1995;Fifth International Workshop on Chromosomes in LeukemiaLymphoma, 1987;Offit et al, 1991). In a previous report (Tien et al, 1993), one of four patients with EBV-associated T-cell malignancies (nasal lymphoma was not included in that study) showed isodicentric chromosome 6, idic(6)(pter !…”
Section: Discussionmentioning
confidence: 97%
“…This finding agrees well with the data from other studies, in which MYC translocations were found in up to 13% of cases. 6,[21][22][23][24][25] It is especially interesting to note that the incidence of MYC + cases was the same in the FL/LCC subtype as in the FL3B and DLBCL/FL3B subtypes, making MYC a likely candidate as a progression factor also in "non-transformed" FL. Out of 12 cases of FL with MYC gene translocation, five cases presented with concurrent translocations of either BCL2 or BCL6, while one case of FL3B showed a triple hit of MYC, BCL2 and BCL6.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent chromosomal aberrations are specifically associated with different lymphoma types [32][33][34] and can serve as diagnostic or prognostic markers. [35][36][37] Furthermore, they may be useful for elucidating disease development and progression.…”
Section: Discussionmentioning
confidence: 99%